2009
DOI: 10.4049/jimmunol.0804096
|View full text |Cite
|
Sign up to set email alerts
|

Important Role for CC Chemokine Ligand 2-Dependent Lung Mononuclear Phagocyte Recruitment to Inhibit Sepsis in Mice Infected with Streptococcus pneumoniae

Abstract: The monocyte chemoattractant CCL2 is of major importance in inflammatory monocyte recruitment to the lungs in response to bacterial infection. Streptococcus pneumoniae is the most prevalent pathogen in community-acquired pneumonia causing significant morbidity and mortality worldwide. In the current study, we examined the role of CCL2 in lung-protective immunity against two strains of S. pneumoniae exhibiting different virulence profiles. Both wild-type mice and CCL2 knockout (KO) mice became septic within 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 23 publications
6
67
3
Order By: Relevance
“…45 Our gating strategy distinguishes ExMs from AMs, which are both CD11c ϩ AF ϩ on the basis of CD11b expression (present on ExMs and absent on AMs), as recently described. [33][34][35][36] In those studies, ExMs were specifically identified in the lungs of mice with bacterial or viral pneumonia, in which the numbers were much smaller than in the current study. The impressive quantity of ExMs that we identify in this model likely reflects the substantial inflammation induced by cryptococcal lung infection, with recruitment of up to 100 million CD45 ϩ leukocytes per mouse and critical reliance on lung macrophages for clearance of this organism.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…45 Our gating strategy distinguishes ExMs from AMs, which are both CD11c ϩ AF ϩ on the basis of CD11b expression (present on ExMs and absent on AMs), as recently described. [33][34][35][36] In those studies, ExMs were specifically identified in the lungs of mice with bacterial or viral pneumonia, in which the numbers were much smaller than in the current study. The impressive quantity of ExMs that we identify in this model likely reflects the substantial inflammation induced by cryptococcal lung infection, with recruitment of up to 100 million CD45 ϩ leukocytes per mouse and critical reliance on lung macrophages for clearance of this organism.…”
Section: Discussioncontrasting
confidence: 61%
“…33,34 In contrast, ExMs express little MHC class II or CD86 in the lungs of mice infected with Streptococcus pneumoniae, an extracellular bacterial pathogen cleared primarily by innate mechanisms. 35 We further show that expression of macrophage-associated proteins and costimulatory molecules is not uniform but varies at different times after infection. Collectively, these data imply that the ExM phenotype may vary according to the following: i) the class of infecting pathogen, ii) whether innate or adaptive immune mechanisms are required for microbial clearance, and iii) the inflammatory milieu within the pulmonary microenvironment during different phases of infection.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Cell turnover rate is slow (11) and is maintained by constitutively immigrating CCR2 2 Gr-1 2 resident monocytes (12,13). In contrast, CCR2 + Gr-1 + inflammatory monocytes rapidly migrate into alveolar airspaces after lung infection and are believed to be the main effectors of acute lung injury and infection-related mortality (6,14,15). Increased AMFs, however, are correlated with the severity of chronic obstructive pulmonary disease (COPD) (16), a debilitating chronic condition characterized by progressive irreversible airflow limitation and lung parenchyma destruction.…”
mentioning
confidence: 99%